Crystal structure, magnetism, and dielectric properties based on the axially chiral ligand 2, 2′-dinitro-4, 4′-biphenyldicarboxylic acid. Issue 11 (24th February 2016) - Chen, Li-Zhuang; Pan, Qi-Jian; Cao, Xing-Xing; Wang, Fang-Ming
Abstract : Six novel metal–organic-frameworks based on axially chiral ligand nbpdc have been synthesized under hydrothermal conditions and studied on gas adsorption, magnetic properties and dielectric properties. Abstract : Six novel metal–organic-frameworks (MOFs), [Ni(nbpdc)(4, 4′-bpy)(H2 O)] n (1 ), [Ni2 (nbpdc)2 (4, 4′-bpy)2 (H2 O)2 ] n (2 ), [Ni(nbpdc)(4, 4′-bpy)] n (3 ), [Mn(nbpdc)(4, 4′-bpy)] n (4 ), [Co(nbpdc)(4, 4′-bpy)] n (5 ), and [Zn2 (nbpdc)2 (4, 4′-bpy)] n (6 ), with different crystal structures and divalent cations (Zn(ii ), Ni(ii ), Mn(ii ), and Co(ii )) from the same ligands nbpdc and 4, 4′-bpy (H2 nbpdc = 2, 2′-dinitro-4, 4′-biphenyldicarboxylic acid, 4, 4′-bpy = 4, 4′-bipyridine) have been synthesized and characterized. Complex1 showed a new point group of 222 and a new topology structure ofsqc6 . Crystal structures of complexes2–6 with the same nonpolar point group of 2/ m were determined by single-crystal X-ray diffraction. Complex2 exhibited a rare three-interlude 3D structure with (4 4 ·6 2 )(4 8 ·6 6 ·8) topology. Complexes3–5 featured the same topology structure of (4 4 ·6 10 ·8)(4 4 ·6 2 ). Complex6 had a 3D framework with (10)(6·8 2 ·10 3 ·12 4 )2 (6 2 ·8)2 (8)2 topology. In addition, complex1 displayed commendable adsorption of N2 at room temperature.4 and5 showed antiferromagnetism. Moreover, all six MOFs displayed abnormal dielectric peaks from 225 K to 275 K, which were measured at various frequencies and temperatures.